Tapered plastic optical fiber sensors for chemical detection and relative humidity measurements / Malathy Batumalay - Malathy, Batumalay (2014)
The developments of novel tapered plastic optical fibers (POFs) devices have become the central focus of researches in recent years especially for sensing applications. In this thesis, simple sensors are proposed and demonstrated using a bare tapered polymethyl methacrylate (PMMA) fiber and tapered PMMA coated sensitive materials for various measurements. The tapered PMMA fibers were fabricated by etching method using acetone, sand paper and de-ionized water to achieve a waist diameter of 0.45 mm and tapering length of 10 mm and operate based on intensity modulation technique. Evanescent field absorption sensors were developed for various electrolyte and nonelectrolyte solutions using the PMMA tapered fiber probe. To enhance the performance of the sensing probe, tapered PMMA fibers were coated with sensitive materials such as graphene polymer, single walled carbon nanotubes polyethylene oxide (SWCNT-PEO) composite and zinc oxide nanostructures for sensing different concentration of uric acid. Subsequent performance analysis allows the identification of the experimental dependence of the surrounding refractive index sensitivity on the three different sensitive coating materials. It is observed that the transmitted light intensity improves with the sensitive material coating. The fiber itself can play an active role by acting as a sensor when the cladding is replaced with chemical sensitive material. On the other hand, RH sensors have been proposed and demonstrated using tapered PMMA in conjunction with various sensitive coating materials such as agarose gel, Hydroxyethylcellulose/ polyvinylidenefluoride (HEC/PVDF) and zinc oxide (ZnO). It is observed that the probe sensitivity improves with the sensitive coating materials. When the composite are exposed to an environment of humidity, it causes rapid surface adsorption of water molecules and changes its optical property. Furthermore, the proposed sensors also provide numerous advantages such as simplicity of design, low cost of production, higher mechanical strength and easier to handle compared to silica fiber optic. PMMA based sensor can easily be automated and to operate at room temperature and varying pressure conditions.